Proinflammatory diet is associated with increased risk of squamous cell head and neck cancer. Issue 7 (26th July 2018) - Mazul, Angela L.; Shivappa, Nitin; Hébert, James R.; Steck, Susan E.; Rodriguez‐Ormaza, Nidia; Weissler, Mark; Olshan, Andrew F.; Zevallos, Jose P.
Abstract : Diets high in fruits and vegetables and low in red meat intake have been associated with decreased risk of head and neck cancer. Additionally, chronic inflammation pathways and their association with cancer have been widely described. We hypothesized a proinflammatory diet, as measured by the dietary inflammatory index (DII ® ), is associated with increased risk of head and neck cancer. We used the Carolina Head and Neck Cancer (CHANCE) study, a population‐based case–control study of head and neck squamous cell carcinoma. Cases were recruited from a 46‐county region in central North Carolina. Controls, frequency‐matched on age, race, and sex were identified through the North Carolina Department of Motor Vehicle records. The DII score, adjusted for energy using the density approach (E‐DII), was calculated from a food frequency questionnaire and split into four quartiles based on the distribution among controls. Adjusted odds ratios (ORs) were estimated with unconditional logistic regression. Cases had higher E‐DII scores (i.e., a more proinflammatory diet) compared with controls (mean: −0.14 vs . −1.50; p value < 0.001). When compared with the lowest quartile, the OR for the highest quartile was 2.91 (95% confidence interval (CI): 2.16–3.95), followed by 1.93 (95% CI: 1.43–2.62) for the third quartile, and 1.37 (95% CI: 1.00–1.89) for the second quartile. Both alcohol and smoking had a significant additive interaction with E‐DII (smoking relative excess risk due to interaction (RERI): 2.83; 95% CI: 1.36–4.30 and alcohol RERI: 1.75; 95% CI: 0.77–2.75). These results provide additional evidence for the association between proinflammatory diet and head and neck cancer. Abstract : What's new? Chronic inflammation is a hallmark of cancer and is influenced by diet. Moreover, specific dietary factors are known to contribute directly to the excess production of proinflammatory factors, thereby fueling the processes of tumor initiation and progression. In this study, proinflammatory dietary factors were investigated in the context of head and neck squamous cell carcinoma (HNSCC). A dietary inflammatory index score was calculated for HNSCC patients based on information from a food frequency questionnaire. HNSCC risk was found to be linearly associated with a proinflammatory diet. Smoking and alcohol consumption interacted with a proinflammatory diet to heighten risk.